The Use of Spiral Computerized Tomography in the Diagnosis of Middle –Third Facial Fractures as Compared to Plain Radiography - Ziarah, *Haithem A; Rassam, Fawaz A; Philip, Ninos P (AL-Kindy College Medical Journal, 2006)
Background: Trauma is one of the most common clinical problems that confront the maxillofacial surgeon and radiologist alike. Middle third facial fractures are diagnosed primarily on the bases of clinical examination and plain radiographs than can result in much preoperative speculation. Objective: To assess the advantages of spiral computerized tomography over conventional radiography in the pre-surgical evaluation of middle third facial fractures. Methods: Thirty patients with thirty-eight facial fractures were studied, all patients were examined clinically, by plain radiography and then by spiral CT. Results: Of the 38 middle-third fractures, 16 (42.1%) were zygomatic fractures, 8 (21.1%) were LeFort fractures, 6 (15.8%) were residual deformities, 4 (10.5%) were orbital blow-out fractures and 4 (10.5%) were naso-ethmoidal injuries. Conclusion: Improved diagnosis of fracture lines, specific patterns of comminution in mid-face fractures, direction of displacement of fracture fragments and the associated soft tissue changes made possible with spiral CT.